Jack London : uma precoce prática etnográfica em O povo do abismo e O cruzeiro do Snark - Mantovani, Marcos (My University, 2015)
This dissertation analyses two non-fiction books written by Jack London: The people of the abyss (published in 1903) and The cruise of the Snark (published in 1911). Written over a period during which ethnography’s construction hadn’t been systematically elaborated yet, we aim to interpret these books as having some characteristics of ethnographic narratives, according to the interpretative anthropology. As theoretical support, the precepts of ethnographic exercise are observed, according to authors like Clifford Geertz, James Clifford, Franz Boas, Bronislaw Malinowski and Roberto DaMatta. To establish the context of this research, we analyze the socio-cultural realities of the USA during the life of Jack London (1876 – 1916), as well as the characteristics of anthropology at the end of the 19th century and at the beginning of the 20th.
Esta dissertação analisa duas obras não ficcionais de Jack London: O povo do abismo (publicada em 1903) e O cruzeiro do Snark (publicada em 1911). Escritas em um período cuja construção da etnografia não havia sido ainda sistematicamente pensada, buscamos interpretar nessas obras algumas características de narrativas etnográficas, a partir da antropologia interpretativa. São observados, como suporte teórico, os preceitos do exercício etnográfico, segundo autores como Clifford Geertz, James Clifford, Franz Boas, Bronislaw Malinowski e Roberto DaMatta. Para que contextualizemos esta pesquisa, são abordadas as realidades socioculturais dos Estados Unidos durante o período de vida de Jack London (1876 – 1916), assim como as características da antropologia no final do século XIX e início do século XX.
Keywords: London, Jack, 1876-1916 - Crítica e interpretação; Etnologia; Antropologia; London, Jack, 1876-1916 - Criticism and interpretation; Ethnology; Anthropology